Toward controlled thermoelectric properties of Pb and Sb co-doped nanostructured Thallium Telluride for energy applications. (21st October 2020) - Khan, Waqas Muhammad; Rahman, Altaf Ur; Tufail, Muhammad; Ibrar, Muhammad; Shah, Wiqar Hussain; Syed, Waqar Adil; Gul, Banat
Abstract: Here, the structure-dependent electronic, thermal, and transport properties of nanostructured thallium telluride (Tl8 Pb x Sb2− x Te6 ) through controlled variation in Pb and Sb (x = 1.96, 1.97, 1.98, 1.99) concentrations have been investigated. In the temperature and concentration-dependent electrical conductivity measurements, the highest electrical conductivity 131.96 × 10 3 Ω − 1 m − 1 at 300 K was measured for x = 1.99 and the maximum observed Seebeck value for the optimized Tl8 Pb1.96 Sb0.04 Te6 nanoparticles was 110.7 μ V/K at 550 K. Such an increased value of the Seebeck coefficient led to the achievement of a significantly improved high-power factor, which was found to be increasing with temperature and decreasing with the increase of Pb concentration. The density functional theory calculations performed for Pb and Sb co-doped Tl5 Te3 resulted in the enhanced σ e and S with a significant reduction in electronic thermal conductivity ( κ e ) and is found consistent with experimentally measured κ e . The highest ZT = 0.35 and 0.18 were recorded experimentally and theoretically for Pb and Sb co-doped in Tl5 Te3 nanoparticles.